Management of corporate responsibility in the business environment: Socio-psychological aspect - Dmytrenko, M.; Nesterenko, Svitlana; Нестеренко, Світлана Анатоліївна; Нестеренко, Светлана Анатольевна; Oleksenko, Roman; Олексенко, Роман Іванович; Олексенко, Роман Иванович; Yeremenko, Larysa; Єременко, Лариса В'ячеславівна; Еременко, Лариса Вячеславовна; Vasylchenko, Olena; Васильченко, Олена Олегівна; et al. (My University, 2021)
The article considers the methodological approach and recommends practical provisions for the management of corporate responsibility of professionals in the business environment, taking into account the socio-psychological components that ensure the trajectory of stable professional development in the food market. It is substantiated that the trajectory of professional stability with a corporate consciousness of development is not a process of continuous action, but a consistent and purposeful project with a certain result, limited in time and resources. Dividing activities into a series of projects allows specifying goals, increasing the accuracy of plans and forecasts. Social trust becomes a certain basis for understanding social relations and responsibility for the process of integration of professional development and stable business activities in the market. The psychological support of stable professional development of employees of the enterprise with corporate responsibility of the business environment is developed. Guidelines and standardized norms of the management at “professional mobility – professional stability” are defined. Signs of intensification of professional development of specialists of the enterprise on the scale of psychological well-being are interpreted. Empirical procedures for qualitative and quantitative analysis of the integral components of the professional potential of employees of the enterprise with a certain level management of corporate responsibility in the business environment are presented. A methodical approach to determining the level of influence of the social component on the corporate responsibility of professional specialists of the enterprise in the market business environment is proposed.
Keywords: Society; Social responsibility; Corporate responsibility; Psychology of professional development; Enterprise